Knowledge, Attitudes, Condom Use among HIV-Positive Men Who Have Sex with Men in Surakarta - Wulansari, Galuh; Juanda Dewi Bambang Bangun Wibowo, Shaviera; Ayu Setyani, Rizka; Ristaning Belawati, Yeny; Natalia Probandari, Ari; Subronto, Yanri Wijayanti; Sitorus, Rico Januar; Widyaningsih, Vitri (International Journal of Health Literacy and Science, 2025)
The prevalence of Human Immunodeficiency Virus (HIV) in Indonesia continues to increase, particularly among men who have sex with men (MSM). Condom use remains a key strategy to prevent HIV transmission in this population. This study aimed to analyze factors associated with consistent condom use among HIV-positive MSM in Surakarta, Indonesia. A cross-sectional design was applied using purposive sampling, involving 34 HIV-positive MSM recruited from the community. Data were collected through a structured questionnaire assessing condom knowledge, attitudes, and use, and analyzed using univariate and bivariate analyses. The mean age was 33 years, with most participants being single (82.3%) and having completed high school to university (94.1%). While 97.1% acknowledged the importance of condoms, 67.6% had misconceptions about correct use, 29.4% perceived condoms as reducing sexual pleasure, and 35.3% reported inconvenience in purchasing or carrying condoms. Only 44.1% reported consistent condom use, and 50.0% had engaged in unprotected sex in the past six months. Bivariate analysis showed no significant association between age, education, marital status, and employment and consistent condom use. These findings highlight the important role of cognitive and attitudinal factors in shaping condom use behavior among HIV-positive MSM, suggesting that targeted behavior change interventions that address misconceptions and sociocultural barriers are crucial for strengthening HIV prevention efforts in Indonesia.